2003
DOI: 10.1889/1.1832534
|View full text |Cite
|
Sign up to set email alerts
|

48.1: A Novel Method for Image Contrast Enhancement in TFT‐LCDs: Dynamic Gamma Control (DGC)

Abstract: This paper describes a novel method for image contrast enhancement by controlling gamma curve in AMLCD. The key idea is to automatically manipulate gamma voltage in accordance with the image data distribution. This method is applied to 17″ SXGA LCD monitor module. The contrast ratio and the brightness are enhanced by about 3 times and 1.7 times, respectively, by using the proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For example, dark images may have a dark stretch curve applied to them. Examples of this type of approach can be found in [1], [2] and [3]. In a video system which has a gamma look up table (LUT), the LUT has been used to implement the contrast look up function.…”
Section: Summary Of Existing Techniquesmentioning
confidence: 99%
“…For example, dark images may have a dark stretch curve applied to them. Examples of this type of approach can be found in [1], [2] and [3]. In a video system which has a gamma look up table (LUT), the LUT has been used to implement the contrast look up function.…”
Section: Summary Of Existing Techniquesmentioning
confidence: 99%
“…The problem, inherent to this technique, is that the brightness of the image will also increase in images that are strongly contrast enhanced and where most of the pixel values are near the bottom of the brightness range. As an example [2] it has been shown that boosting the dark regions contrast results in a 3X improvement in Contrast Ratio and a 1.7X increase in brightness. This brightness increase creates a problem by changing the brightness dynamics of the film content.…”
Section: Gamma and Backlight Optimizationmentioning
confidence: 99%
“…They tested the regular change between grayscale voltage and luminance on the panel without gamma correction to collect the brightness curve, then interpolated the data of second panel using a nonlinear DAC to obtain another brightness curve, and the final step is to find the relationship curve between the brightness and the gray level voltage by matching those two curves according to the curve of ideal perceived brightness by the human eyes. Haeng et al [4] . used a dynamic voltage method to process the gamma curve so that the voltage and brightness are dynamically balanced and the grayscale voltage could change in real-time with the brightness.…”
Section: Introductionmentioning
confidence: 99%